The Rhyacophila fasciata Group in Greece: Rhyacophila kykladica Malicky & Sipahiler 1993 (stat. prom.) (Trichoptera: Rhyacophilidae). Morphological description, genetic and ecological features - Valladolid, Maria; Karaouzas, Ioannis; Arauzo, Mercedes; Dorda, Beatriz A.; Rey, Isabel (Zootaxa, 2019)
The morphology of the different stages (larva, pupa, male, and female) of Rhyacophila fasciata kykladica Malicky & Sipahiler 1993 was examined as a basis for the description of the taxon. Morphological data were supplemented by molecular analysis of mitochondrial cytochrome C oxidase subunit I (mtCOI), which were compared with samples of the nominate subspecies Rhyacophila fasciata fasciata Hagen 1859, as well as with other new species in this group, Rhyacophila denticulata McLachlan 1879 and Rhyacophila sociata Navás 1916. Our results revealed genetic differences between all the taxa; therefore, a change of taxonomic status of R. fasciata kykladica to R. kykladica (stat. prom.) is proposed.